Digital Transformation and Small Business Performance - Hadady, Hartaty; Saleh, Iksan M (International Journal of Business, Law, and Education, 2023)
This study aims to examine the relationship between digital transformation and small business performance. This research was conducted in June-July 2023 in Ternate City. The population in this study are all business actors in the city of Ternate. The sample in this study was determined with the condition that to become a respondent, the status of a business leader with total assets of no more than 500 million rupiah and already traded health and care products online. For this reason, the number of respondents involved in this survey was 104 people. The research hypothesis was tested with a simple linear regression analysis statistical tool. The test results indicate confirming the proposed hypothesis. Furthermore, the conclusions and limitations of recommendations for future research are also discussed